Resilience: A New Paradigm of Nuclear Safety: From Accident Mitigation to Resilient Society Facing Extreme Situations - Ahn, Joonhong; Guarnieri, Franck; Furuta, Kazuo (Springer Nature, 2017)
nuclear safety; decision making